2022
DOI: 10.3390/agronomy12102531
|View full text |Cite
|
Sign up to set email alerts
|

LED Lighting Effects on Plant Growth and Quality of Pyrus communis L. Propagated In Vitro

Abstract: Fluorescent lights are typically used as light source in indoor horticultural production, including micropropagation. However, light emitting diodes (LEDs) have been recently used for plant growth under controlled environment. Major advantage of LEDs is wavelength specificity, that allows to adequately adjust the spectra according to plant needs. The possibility of using LED as primary light source for the micropropagation of Pyrus communis L. has been investigated in this work. It was proceeded to the optimiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Currently, micropropagation is used for the multiplication of rootstocks and cultivars in several fruit species, such as pear, kiwi, banana, pineapple, and others [ 3 ]. Nowadays, the main challenges for micropropagation are represented by cost reduction: for example, using LED systems, efficiency enhancement, ex vitro rooting, use of plastic-free or biodegradable containers, and combining micropropagation with other systems/propagation techniques that can extend its application by replacing the conventional propagation techniques and technologies [ 9 , 10 , 11 , 12 ]. However, in the case of olive trees, only a very small percentage of plants is obtained through micropropagation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, micropropagation is used for the multiplication of rootstocks and cultivars in several fruit species, such as pear, kiwi, banana, pineapple, and others [ 3 ]. Nowadays, the main challenges for micropropagation are represented by cost reduction: for example, using LED systems, efficiency enhancement, ex vitro rooting, use of plastic-free or biodegradable containers, and combining micropropagation with other systems/propagation techniques that can extend its application by replacing the conventional propagation techniques and technologies [ 9 , 10 , 11 , 12 ]. However, in the case of olive trees, only a very small percentage of plants is obtained through micropropagation.…”
Section: Introductionmentioning
confidence: 99%
“…Among the substances of natural origin that can potentially be added to growth media for olive in vitro propagation, there is neem oil also. Indeed, a previous article, [ 10 ] demonstrated that the addition of neem oil to an Olive Medium (OM) containing zeatin (4 mg L −1 ) increased the shoot length, the number of nodes, and the fresh and dry weight of shoots of olive cultivar Moraiolo.…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of solid-state lighting, white light-emitting diodes (WLEDs) hold immense promise owing to their energy efficiency and environmentally benign attributes, favorable luminous efficacy, as well as their uncomplicated and easily fabricable structures. These light sources find applications in diverse fields, such as plant growth illumination, signaling and indicator lamps, and flat-panel displays. Nevertheless, conventional organic phosphor resin converters suffer from obvious drawbacks, including inadequate thermal stability, low thermal conductivity, and susceptibility to aging-induced degradation and phosphor corrosion. These issues collectively lead to reduced efficiency of white light emission from the WLEDs and shortened operational lifespan of the devices. …”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are many studies demonstrating the effects of LEDs with different wavelengths (colors) on the in vitro development of Vitis riparia (Poudel et al 2008), cotton plant (Li and Tang, 2010), Cedrela ssilis (Tadeu, 2017), Helianthus tuberosus (Seedapalee et al 2021), Ficus carica var. Black Jack (Parab et al 2021), Pyrus communis (Lupo et al 2022), Pinus pseudostrobus (Marín-Martinez and Iglesias-Andreu, 2022). Gupta and Jatothu (2013) reported the best development of crops without the induction of damage or photo stress.…”
Section: Introductionmentioning
confidence: 99%